PENGARUH PRICE DISCOUNT TERHADAP ONLINE IMPULSE BUYING DENGAN POSITIVE EMOTION SEBAGAI VARIABEL MEDIASI - Wijana, I Made Michael; Nandya Oktora Panasea, I Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The purpose of this study is to explain the role of positive emotion in mediating the effect of price discount on online impulse buying. This research was conducted in Denpasar City. The number of population used in this study is infinite (not limited). The sample was taken as many as 110 respondents through purposive sampling method and distributed using a google form questionnaire with adjusted criteria. Measured by 11 indicators and using a Likert scale. The data analysis technique used is path analysis and Sobel test. The results of this study indicate that all hypotheses are accepted. Price discount has a positive and significant effect on online impulse buying. Price discount has a positive and significant effect on positive emotion. Positive emotion has a positive and significant effect on online impulse buying. Positive emotion plays a significant role in mediating the effect of price discount on online impulse buying. The results of this study indicate that in increasing online impulse buying, the management of the Berry Benka is expected to always provide promotional strategies in the form of discount prices to touch consumers' hearts and create positive emotions when shopping.